Mucocutaneous manifestations of Epstein-Barr virus infection (2008)
This review focuses on Epstein-Barr virus (EBV) infection, diagnosis, and current treatment, with emphasis on EBV-associated mucocutaneous manifestations in primary infections, acute EBV-associated syndromes, chronic infections, lymphoproliferative disorders, and lymphomas. In primary infection, EBV infects B cells and can cause mucocutaneous manifestations in infectious mononucleosis or acute EBV-associated syndromes such as Gianotti-Crosti syndrome and hemophagocytic syndrome. EBV then persists in the majority of humans generally without causing disease. In some cases, however, latent EBV infection may result in diseases such as hydroa vacciniforme, hypersensitivity to mosquito bites, and lymphoproliferative disorders such as plasmablastic lymphoma, oral hairy leukoplakia, and post-transplant lymphoproliferative disorders, particularly in immunocompromised patients. Latent EBV infection has also been implicated in a variety of malignant conditions such as Burkitt lymphoma, Hodgkin lymphoma, nasopharyngeal carcinoma, and Kikuchi histocytic necrotizing lymphadenitis. Since the immune system is critical in preventing the progression of EBV disease, the immunologic status of the patient plays a crucial role in the subsequent development of pathologies.